Imagining Germany abroad, c. 1920-1950. Women writers, photographers, exiles, Nazis - Friege, K (2023)
This thesis explores the lives of a small selection of individual German women who pursued professions as writers, journalists, or photojournalists, and whose work saw them spend significant periods of time abroad between 1920 and 1950. These women were unalike in important ways: they held diverging political beliefs, pursued different personal and professional goals, and travelled abroad in contradictory directions. At the same time, they shared a strong sense of independence and individuality, unanimously considered themselves to be modern women, and were each committed to their own imagined version of the German nation.